Association of B-Type Natriureteric Peptide Levels With Estimated Glomerular Filtration Rate in Different Stages of Chronic Kidney Disease And Relevant Echocardiographic Changes (Anwer Khan Modern Medical College Journal, 2018)
Background: B-type natriuretic peptide (BNP) is a biomarker of cardiovascular disease that is common in patients with chronic kidney disease (CKD). The influence of glomerular filtration rate (GFR) on BNP in CKD may stem from failure to account fully for the effects of coexistent cardiac disease, dysfunction and volume overload.Material & Methods: This is a cross sectional descriptive type of observational study conducted by the Department of Nephrology of Anwer Khan Modern Medical College Hospital during the period of Jan 2016 to Dec 2016.Results: A total number of 71 patients were included in the study. Out of them 42(59.15%) were male and 29(40.85%) were female with a M:F of 1.45:1. The mean age of the patients was 62.54+13.92 years (Range 18- 90 years). Mean e GFR was 21.81+15.01 ml/min/1.73 body surface area, mean Serum Creatinine was 5.04+3.29 mg/dl, mean Hb% was 10.90+1.5 gm/dl and that of BNP was 1335.03+1838.43 Pg/ml and that of Ejection Fraction (EF) was 50.05+12.61%. 21.12%(15) were on Stage 3 CKD(Chronic Kidney Disease) and 33.80% (24) and 45.08%(32) were on Stage-4 and Stage-5 respectively.There was a strong and highly significant inverse association between BNP and e GFR (p